(untitled) (Journal of Dhaka Medical College, 2024)
Background: Lateral epicondylitis, is prevalent in the world of sports; however, this injury still causes confusion among healthcare professionals. Numerous studies have evaluated treatment options, but few have taken into consideration the extent to which tennis players, themselves, understand this ailment. Objectives: To identify the risk factors associated with lateral epicondylitis. Materials and methods: An observational case control study design was carried out among 120 patients attended at outdoor Department of Physical Medicine and Rehabilitation, BSMMU, Dhaka from April 2018 to march 2019. Sixty (60) patients with lateral epicondylitis as case group and another 60 patients without lateral epicondylitis as control group. Data was collected using a structured interviewer- administered questionnaire, enquiring about demographic data and details of risk factors. Result: The mean age was found 39.4:6.3 years in case group and 36.97.4 years in control group. Twenty- seven (45.0%) patients had more than 2 hours of use hand in case group and 12(20.0%) in control group. More than half (53.3%) patients had moderate VAS scale in case group and 9(15.0%) in control group, Nine (15.0%) patients were found past history of recurrent injury in case group and not found in control group. The difference was statistically significant (p<0.05) between two groups. Patients having use hand more than 2 hours 3.273 (95% CI 1.453% to 7.36%) times more likely to developed lateral epicondylitis. Conclusion: Use of hand with repetitive wrist extension more than 2 hours was significantly associated with lateral epicondylitis. J Dhaka Med Coll. 2023; 32(1) : 77-84